2010
DOI: 10.2119/molmed.2010.00111
|View full text |Cite|
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme (ACE) 2 Overexpression Ameliorates Glomerular Injury in a Rat Model of Diabetic Nephropathy: A Comparison with ACE Inhibition

Abstract: The reduced expression of angiotensin-converting enzyme (ACE) 2 in the kidneys of animal models and patients with diabetes suggests ACE2 involvement in diabetic nephrology. To explore the renoprotective effects of ACE2 overexpression, ACE inhibition (ACEI) or both on diabetic nephropathy and the potential mechanisms involved, 50 Wistar rats were randomly divided into a normal group that received an injection of sodium citrate buffer and a diabetic model group that received an injection of 60 mg/kg streptozotoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
86
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 43 publications
(46 reference statements)
6
86
0
1
Order By: Relevance
“…Tikellis et al [10] have also demonstrated that ACE2 is decreased in the diabetic tubule. Consistent with this, ACE2 overexpression has been reported to have a renoprotective effect since it prevents experimental diabetic glomerular injury [11]. However, the mechanisms for a reduction in ACE2 being associated with kidney disease, including the progression of diabetic nephropathy, have still to be fully clarified.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Tikellis et al [10] have also demonstrated that ACE2 is decreased in the diabetic tubule. Consistent with this, ACE2 overexpression has been reported to have a renoprotective effect since it prevents experimental diabetic glomerular injury [11]. However, the mechanisms for a reduction in ACE2 being associated with kidney disease, including the progression of diabetic nephropathy, have still to be fully clarified.…”
Section: Introductionmentioning
confidence: 67%
“…For example, Shah et al [12] have demonstrated that the blockage of NPR-A in the heart diminished the antihypertrophic effect of Ang-(1-7). Interestingly, given the renoprotective paracrine effects of ANP [14][15][16]37], the finding that ACE2 increases ANP in vitro could also explain why overexpression of ACE2 in diabetic mice results in amelioration of their glomerular injury [11]. Thus we speculate that the benefit of reintroducing ACE2 in diabetic mice might partly be due to an expected increase in renal ANP levels.…”
Section: Discussionmentioning
confidence: 88%
“…Increased oxidative stress may contribute to LV remodeling and dysfunction in heart failure (Watanabe et al, 2006;Korantzopoulos et al, 2003). Recent study reported that local RAS was highly activated, as manifested by increased ACE expression and ANG-II level, and decreased ACE-2 expression and ANG 1-7 level in the heart (Liu et al, 2011). As the key peptide of the RAS, ANG-II exerts a variety of effects via its type 1 receptor, including vasoconstriction, sodium retention, cell proliferation and apoptosis, proinflammation and oxidative stress (Oudit et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A down-regulation of ACE2 is observed in diabetes (Wong et al, 2007) while, administration of Ang-(1-7) in diabetic rat reduced proteinuria and restored renal vascular responses (Benter et al, 2007). An ACE2 over-expression is observed to ameliorate (Liu et al, 2011). Currently, the effects of Ang-(1-7) in the kidney have not been fully understood and are still in debate.…”
Section: Introductionmentioning
confidence: 99%